The Influence of the Structure Parameters on the Extensibility of Woven Fabrics - Klevaityte, Ramune; Sacevičienė, Virginija; Masteikaitė, Vitalija; Urbelis, Virginijus (Jaunųjų mokslininkų darbai, 2020)
Fabric deformation properties considerably depend on its structure. Garment elasticity is an important factor that allows a garment wearer to move freely. Fabric deformation depends on the structure parameters of yarrn and fabric. It has been known that elongation at break of fabric with elastane yarn is higher than of ordinary fabric. The aim of this work was to analyse elongation at break parameters of the and warp and weft yarn in fabrics. Ten commercially produced samples of woven fabrics were used in the experiment. Some samples were with elastan yarn in the warp and weft directions or only in the weft direction. Elongation at break was measured applying a standard method. The results showed that elongation at break of the main elastic component or another component may occur simultaneously when an elastic component or elastane yarn may reach fabric ultimate elongation.